2014
DOI: 10.1111/tpj.12441
|View full text |Cite
|
Sign up to set email alerts
|

Major repeat components covering one‐third of the ginseng (Panax ginseng C.A. Meyer) genome and evidence for allotetraploidy

Abstract: SUMMARYGinseng (Panax ginseng) is a famous medicinal herb, but the composition and structure of its genome are largely unknown. Here we characterized the major repeat components and inspected their distribution in the ginseng genome. By analyzing three repeat-rich bacterial artificial chromosome (BAC) sequences from ginseng, we identified complex insertion patterns of 34 long terminal repeat retrotransposons (LTR-RTs) and 11 LTR-RT derivatives accounting for more than 80% of the BAC sequences. The LTR-RTs were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
79
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(83 citation statements)
references
References 85 publications
3
79
1
Order By: Relevance
“…The dissolution flasks were immersed in a water bath at 37°C, filled with 900 mL of 1 M HCl, distilled water or phosphate-buffered saline (pH 6.8). At different time intervals (1,3,5,10,20,30,45, 60 min), 1 mL of dissolution media were withdrawn and filtered using 0.45 µm polyether sulfone membrane filters. One milliliter of fresh media was supplemented into the corresponding flasks.…”
Section: Experimental Materials 20(s)-ppd Was Purchased From Shanghaimentioning
confidence: 99%
See 1 more Smart Citation
“…The dissolution flasks were immersed in a water bath at 37°C, filled with 900 mL of 1 M HCl, distilled water or phosphate-buffered saline (pH 6.8). At different time intervals (1,3,5,10,20,30,45, 60 min), 1 mL of dissolution media were withdrawn and filtered using 0.45 µm polyether sulfone membrane filters. One milliliter of fresh media was supplemented into the corresponding flasks.…”
Section: Experimental Materials 20(s)-ppd Was Purchased From Shanghaimentioning
confidence: 99%
“…1) is one of aglycones of ginsenosides and has a wide range of pharmacological activities, especially in antitumor and neurological function recovery. [4][5][6][7][8] However, the low bioavailability of ginsenosides (1% for Rb 1 , 3.4% for Rb 2 , 1.9% for Rg 1 ) after oral administration restricts their clinical applications. [9][10][11] Importantly, PPD is the final active component after the absorption of ginsenosides in intestine.…”
mentioning
confidence: 99%
“…Numerous studies have shown the indispensable roles of repeats in a genome which include genotypic and phenotypic variations, heterochromatin formation and environmental adaptation (Kalendar et al 2000;Lippman et al 2004;Wei et al 2014). Because repeat amplification or elimination could happen before or after species divergence, repeats can be an excellent tool in studying evolution of genomes (Choi et al 2014;Mehrotra and Goyal 2014;Wei et al 2014). Although different repeats follow different evolutionary pathways, tandem repeats have been evolutionarily associated with other repetitive DNA like transposable elements and the intergenic spacers (IGSs) of the 45S rDNA genes in several plant species (Cheng and Murata 2003;Macas et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Panax ginseng (Korean ginseng or Asian ginseng) is an important allotetraploid (2n = 4x = 48) perennial crop (Choi et al 2014;Jang et al 2017), highly priced for its ginsenoside, which is known to have a wide range of therapeutic effects (Court 2000;Park et al 2012). In addition, its sensitivity to light, slow growth (∼four years/generation) and low seed yield (∼40 seeds/plant) have contributed to its high price and a multi-billion USD market (Baeg and So 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation